Death and love in the Holocaust : the story of Sonja and Kurt Messerschmidt - Hochstadt, Steve, 1948- (Augusta, ME : Holocaust Human Rights Center of Maine, 2012)
Sonja and Kurt Messerschmidt met in Berlin, married in Theresienstadt, and survived Auschwitz. In this book they tell their intertwined stories in their own words, taken from interviews done as part of the Holocaust and Human Rights Center of Maine's larger interview projects. The text directly expresses their experiences, reactions and emotions. By alternating excerpts from interviews, the reader moves through the stages of the Holocaust: Persecution in Berlin, deportation to Theresienstadt, and then to Auschwitz, slave labor, death marches, liberation, reunion, and finally emigration to the US.
Includes sources (p. 99-101) and index.
Keywords: Messerschmidt, Kurt -- Biography; Messerschmidt, Sonja -- Biography; Holocaust, Jewish (1933-1945) -- Biography; World War, 1939-1945 -- Biography